Demografische Alterung führt zu einem stark sinkenden Erwerbspersonenpotenzial; Demographic ageing leads to a sharply declining labour force potential - Johann Fuchs; Doris Söhnlein; Birgit Weber (Wirtschaftsdienst, 2022)
– The demographic development in Germany will lead to a declining number of people of working age and thus potentially in the labour force. The age structure is shifting towards older cohorts. The labour force will decline by 16 million workers between 2020 and 2060. However, an increase in the labour force participation of women and elderly people combined with immigration will mitigate the demographic effect. An average net migration of 100,000 persons per year would result in a projected decline in the labour force of 9 million by 2060. An extremely high migration of at least 400,000 persons would allow the potential labour force to remain roughly constant. A sensitivity analysis also looks at the effects that may arise if the participation rates increased even further.
Keywords: J11; J21; J22; 330; Arbeitskräfte; Ältere Arbeitskräfte; Demographie; Deutschland